Mourning and marijuana: exploring the relation between cannabis and grief among Colorado college students - Smith, Emma E., author; Conner, Bradley T., advisor; Prince, Mark A., committee member; Harvey, Ashley, committee member; Amberg, Marti, committee member (Colorado State University. Libraries, 2025)
Emerging adults consistently report the highest rates of cannabis use globally. Although cannabis is often used to manage distress, coping-motivated use is linked to worsened mental health outcomes, including increased risk for cannabis use disorder (CUD). However, grief as a predictor of cannabis use is underexplored. Prolonged Grief Disorder (PGD) and grief rumination are increasingly recognized as distinct yet interrelated risk factors for psychological impairment. Emotion dysregulation may further exacerbate maladaptive coping tendencies, including substance use. This study investigated whether grief symptoms and grief rumination predict cannabis use frequency and CUD symptoms and whether emotion regulation difficulties moderate these relations. Participants (N = 923; Mage = 19.27, SDage = 2.61) were recruited from introductory psychology courses and completed validated self-report measures of grief (PG-13-R), grief rumination (UGRS), cannabis use (past 30-day use, CUDIT-R), emotion dysregulation (DERS), and cannabis use motives (MMQ). Poisson regression and interaction models were used to test hypothesized relations. Direct effects revealed that while prolonged grief and grief rumination did not significantly predict 30-day cannabis use frequency, elevated grief variables positively predicted increased CUD symptoms at the bivariate level. Further, grief significantly interacted with emotion dysregulation to predict cannabis outcomes. Specifically, individuals with high grief and high emotion dysregulation reported significantly greater cannabis use frequency and CUD symptoms. Marginal effects plots confirmed that grief-related cannabis use was most pronounced among individuals with the greatest emotion regulation difficulties. Results offer novel evidence that grief-related distress predicts more problematic cannabis use patterns in emerging adults—and this relation changes as a function of emotion regulation capacity. The results underscore the potential utility of employing emotion regulation skills in coping with bereavement and suggest a need to address grief as a contributing factor to substance misuse.
Keywords: CUD; grief; cannabis; rumination; emotion